Reconstruction Of â€œObstruction Of Justiceâ€ As A Criminal Act In The Law On Eradicating Corruption In Indonesia - Samsul HUDA; Bambang SUGIRI; Nurini APRILIANDA; Heru R. HADI (Indonesia Strategic Sustainability, 2022)
Corruption is a special criminal act, qualified as an ordinary crime but must be eradicated in extraordinary ways. In Indonesia, it is not only an extraordinary method but also an institution with extraordinary authority formed because corruption has become a systemic and systematic disease of society. Criminalizing the act of